Modulatory Effect of 1,25-Dihydroxyvitamin D3 on IL1β-Induced RANKL, OPG, TNFα, and IL-6 Expression in Human Rheumatoid Synoviocyte MH7A - Xiaoke Feng; Chengyin Lv; Fang Wang; Ke Gan; Miaojia Zhang; Wenfeng Tan (Clinical and Developmental Immunology)
Receptor activator of nuclear factor κB ligand (RANKL) plays a crucial role in the bone erosion of rheumatoid arthritis (RA) by prompting osteoclastogenesis. Considering that 1,25(OH)2D3 has been suggested as a potent inducer of RANKL expression, it should clarify whether vitamin D supplement could result in RANKL overexpression and thereby facilitate excessive osteoclastogenesis and bone resorption in RA. Here, we investigated modulatory effect of 1,25(OH)2D3 on the expression of RANKL and its decoy receptor osteoprotegerin (OPG) in an inflammatory condition of human rheumatoid synoviocyte MH7A. MH7A cells were stimulated with IL1β and then treated with different concentrations of 1,25(OH)2D3 for 48 h. A significantly elevated OPG/RANKL ratio and markedly decreased levels of IL-6 and TNFβ mRNA expression in cells and IL-6 protein in supernatants were observed in IL1β-induced MH7A in the presence of 1,25(OH)2D3 compared with those in the absence of it. Osteoclast formation was obviously decreased when RAW264.7 cells were treated with both 1,25(OH)2D3 and IL1β. In summary, although it has a biological function to induce RANKL expression, 1,25(OH)2D3 could upregulate OPG/RANKL ratio and mediate anti-inflammatory action in an inflammatory milieu of synoviocyte, contributing to the inhibition of inflammation-induced osteoclastogenesis in RA.